Beneficial effect of ursodeoxycholic acid in patients with acyl‐CoA oxidase 2 (ACOX2) deficiency–associated hypertransaminasemia. Issue 5 (1st July 2022) - Alonso‐Peña, Marta; Espinosa‐Escudero, Ricardo; Herraez, Elisa; Briz, Oscar; Cagigal, Maria Luisa; Gonzalez‐Santiago, Jesus M.; Ortega‐Alonso, Aida; Fernandez‐Rodriguez, Conrado; Bujanda, Luis; Calvo Sanchez, Marta; D´Avola, Delia; Londoño, Maria‐Carlota; et al.
Abstract: Background and Aims: A variant (p.Arg225Trp) of peroxisomal acyl‐CoA oxidase 2 (ACOX2), involved in bile acid (BA) side‐chain shortening, has been associated with unexplained persistent hypertransaminasemia and accumulation of C27‐BAs, mainly 3α, 7α, 12α‐trihydroxy‐5β‐cholestanoic acid (THCA). We aimed to investigate the prevalence of ACOX2 deficiency‐associated hypertransaminasemia (ADAH), its response to ursodeoxycholic acid (UDCA), elucidate its pathophysiological mechanism and identify other inborn errors that could cause this alteration. Methods and Results: Among 33 patients with unexplained hypertransaminasemia from 11 hospitals and 13 of their relatives, seven individuals with abnormally high C27‐BA levels (>50% of total BAs) were identified by high‐performance liquid chromatography‐mass spectrometry. The p.Arg225Trp variant was found in homozygosity (exon amplification/sequencing) in two patients and three family members. Two additional nonrelated patients were heterozygous carriers of different alleles: c.673C>T (p.Arg225Trp) and c.456_459del (p.Thr154fs). In patients with ADAH, impaired liver expression of ACOX2, but not ACOX3, was found (immunohistochemistry). Treatment with UDCA normalized aminotransferase levels. Incubation of HuH‐7 hepatoma cells with THCA, which was efficiently taken up, but not through BA transporters, increased reactive oxygen species production (flow cytometry), endoplasmic reticulum stress biomarkers ( GRP78, CHOP, and XBP1‐S/XBP1‐U ratio), and BAXα expression (reverse transcription followed by quantitative polymerase chain reaction and immunoblot), whereas cell viability was decreased (tetrazolium salt‐based cell viability test). THCA‐induced cell toxicity was higher than that of major C24‐BAs and was not prevented by UDCA. Fourteen predicted ACOX2 variants were generated (site‐directed mutagenesis) and expressed in HuH‐7 cells. Functional tests to determine their ability to metabolize THCA identified six with the potential to cause ADAH. Conclusions: Dysfunctional ACOX2 has been found in several patients with unexplained hypertransaminasemia. This condition can be accurately identified by a noninvasive diagnostic strategy based on plasma BA profiling and ACOX2 sequencing. Moreover, UDCA treatment can efficiently attenuate liver damage in these patients. Abstract :